2011
DOI: 10.3144/expresspolymlett.2011.79
|View full text |Cite
|
Sign up to set email alerts
|

Effects of graphene oxides on the cure behaviors of a tetrafunctional epoxy resin

Abstract: The influence of graphene oxides (GOs) on the cure behavior and thermal stability of a tetrafunctional tetraglycidyl-4,4’-diaminodiphenylmethane cured with 4,4’-diaminodiphenylsulfone was investigated by using dynamic differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA). The dynamic DSC results showed that the initial reaction temperature and exothermal peak temperature decreased with the increase of GO contents. Furthermore, the addition of GO increased the enthalpy of epox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
82
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(88 citation statements)
references
References 37 publications
5
82
0
1
Order By: Relevance
“…The maximum degradation temperature, T max , and the temperature of 50% mass loss, T 50% , both remained largely unchanged, see Table 3. The changes observed in T on and W 350 are indicative of decreasing thermal stability with increasing rGO content, although increases in thermal stability with increasing rGO content have also been reported in the literature [11,38].…”
Section: Thermal Stability Of the Nanocompositessupporting
confidence: 55%
“…The maximum degradation temperature, T max , and the temperature of 50% mass loss, T 50% , both remained largely unchanged, see Table 3. The changes observed in T on and W 350 are indicative of decreasing thermal stability with increasing rGO content, although increases in thermal stability with increasing rGO content have also been reported in the literature [11,38].…”
Section: Thermal Stability Of the Nanocompositessupporting
confidence: 55%
“…The existence of O element is due to the oxygen-containing functional groups, which is in good agreement with FT-IR analysis. So pristine GO is not thermally stable, and mass loss starts even below 100°C and is rapidly at 150°C [13,31], which are respectively attributed to evaporation of the remaining water and the decomposition of labile oxygen groups [32]. In contrast, the weight loss of TLCP-g-GO starts at 280°C, which is roughly 130°C higher than that of GO.…”
Section: Resultsmentioning
confidence: 81%
“…have been taken into account; however, the property improvements are still far from expectations and the thermal conductivity in particular [3][4][5]. The polymerization of monomers into the polymer matrix is of vital importance to the final properties of composites, several kinetic works reported the effect of GMs on the polymerization [6][7][8][9][10][11], specifically, Wu et al [6] found a vulcanization stage dependence of activation energy (E) variation of graphene/natural rubber system with Ozawa and Kissinger methods; Wang and Qiu [7] noticed an accelerated isothermal melt crystallization of poly (l-lactic acid) by graphene oxide (GO) with isoconversional method; Jing and Qiu [8] (3-hydroxybutyrate) depends on the GO loading and the crystallization temperature; Zhang et al [9] used Kissinger equation and noticed that GO decreases the E of nylon 6; Qiu et al [10] used isoconversional method and found that the effect of GO on the E of a tetrafunctional tetraglycidyl-4,4"-diaminodiphenylmethane cured with 4,4"-diaminodiphenylsulfone depends on GO content and curing stage; and with Kamal and Ryan's model as well as Isayev and Deng's model, Allahbakhsh et al [11] revealed that E of GO/ethylene-propylene-diene rubber system depends on the GO content and the dispersion quality of GO. Notably, hardly any kinetic works directly contribute to the performance improvement of GM/polymer composites, worse still, the polymerizing strategy for the polymer matrices are extensively misused for the GM/polymer composites.…”
Section: Introductionmentioning
confidence: 99%